PERSEPSI WARGA BELAJAR TERHADAP EFEKTIVITAS PELAYANAN TAMAN BACA MASYARAKAT (TBM) DI SATUAN PENDIDIKAN NON FORMAL (SPNF) SANGGAR KEGIATAN BELAJAR (SKB) KOTA PEKANBARU - Nelly Sundari; Daeng Ayub Natuna; Jaspar Jas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine and analyze the level of Community Reading Park Service Effectiveness (TBM), this research was conducted at the Non-Formal Education Unit (SPNF) of the Pekanbaru City Learning Center (SKB), the variables used were service effectiveness measurement indicators in service effectiveness. yautu prasatana facilities and human resources This study used descriptive statistical analysis with a quantitative approach to one variable The population in this study amounted to 40 citizens learning the equivalence of packages A, B and C. Regardless of the characteristics in the population, Lustramen in this study is a questionnaire or a questionnaire which contains 45 statements about the effectiveness of response which are identified from two indicators. Obtained the mean of the infrastructure and facilities indicator is 2, then the human resource indicator is 4.22 which is classified as high. 77.55 and the remaining 22.75 are influenced by other indicators besides the indicators in this study.Key Words: Perception, Service effectiveness. Community Reading Park